Polyester film and application of the same

The polyester film with tailored optical and mechanical properties addresses image distortion and structural issues in foldable displays, enhancing mass productivity and functionality.

JP2025013543AActive Publication Date: 2025-01-24TOYOBO CO LTD
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
JP2024194565
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2019-07-12
Filing Date
2024-11-06
Publication Date
2025-01-24
Estimated Expiration
2040-01-20

AI Technical Summary

Technical Problem

Conventional foldable displays suffer from image distortion and structural issues such as creases or cracks at the folded portion due to repeated folding, affecting mass productivity and functionality.

Method used

A polyester film for foldable displays with specific refractive index ranges (1.590-1.620 in the bending direction, 1.670-1.700 in the folding direction, and 1.520 or less in the thickness direction, along with a density of 1.380g/cm³, and a total light transmittance of 85% or more, haze of 3% or less, and a maximum thermal shrinkage rate of 6% or less, combined with an easily adhesive layer and a hard coat layer for surface protection.

Benefits of technology

The solution maintains mass productivity and prevents image distortion and structural damage at the folded portion, ensuring high functionality and portability of foldable displays.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025013543000001_ABST
    Figure 2025013543000001_ABST
Patent Text Reader

Abstract

To provide a polyester film for a protective film of a folding-type display, which is unlikely to have cracks in a folding portion, in order to provide a folding-type display that is excellent in mass productivity and that prevents the generation of a distortion in an image displayed on a folded portion after the display is repeatedly folded.SOLUTION: Provided is a polyester film for a protective film of a folding-type display, which satisfies the following conditions: (1) the refractive index in a bending direction is 1.590-1.620; (2) the refractive index in the direction of a folding part is 1.670-1.700; (3) the refractive index in a thickness direction is equal to or less than 1.520; and (4) the density is equal to or greater than 1.380 g / cm3 (here, the bending direction is the direction orthogonal to the folding part when folding the polyester film).SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polyester film for a foldable display, a hard coat film for a foldable display, a foldable display, and a mobile terminal device, and more particularly to a foldable display and a mobile terminal device that are less susceptible to image distortion due to film deformation even when repeatedly folded, and the polyester film and hard coat film for a foldable display. [Background technology]

[0002] As mobile terminal devices become thinner and lighter, smartphones and other mobile terminal devices are becoming more and more popular. While mobile terminal devices are required to have a variety of functions, they are also required to be convenient. For this reason, the mobile terminal devices that are currently in use must be able to perform simple operations with one hand, and must have a small screen size of around 6 inches, since they are assumed to be stored in a pocket or similar.

[0003] On the other hand, tablet devices with screen sizes of 7 to 10 inches are highly functional and can be used not only for video content and music, but also for business purposes, drawing, reading, etc. However, they cannot be operated with one hand, are less portable, and have issues with convenience.

[0004] To achieve these goals, a method has been proposed of connecting multiple displays together to make them more compact (see Patent Document 1), but this method has not become widespread because it leaves a bezel, which means the image is cut off and visibility is reduced.

[0005] In recent years, mobile terminals incorporating flexible displays and foldable displays have been proposed, which provide a large-screen display without interruption to the image and are convenient to carry around.

[0006] Here, in the case of conventional displays and mobile terminal devices that do not have a folding structure, the surface of the display can be protected by a non-flexible material such as glass, but in the case of a folding display, when a one-sided display is formed through a folding part, it is necessary to use a hard coat film that is flexible and can protect the surface. However, in a folding display, the part corresponding to a certain folding part is repeatedly folded, so that the film in that part deforms over time, causing problems such as distorting the image displayed on the display. In addition to the surface protection film, films are used in various parts of the folding display, such as polarizing plates, retardation plates, touch panel substrates, substrates of display cells such as organic EL, and protective members on the back surface, and durability against repeated folding is also required for these films.

[0007] In view of this, a method has been proposed in which the film thickness is partially changed (see Patent Document 2), but this method has the problem of being poorly suited for mass production.

[0008] A method of adjusting the refractive index in the bending direction of a polyester film has also been proposed (see Patent Document 3), but as the refractive index in the bending direction is reduced, the pencil hardness when a hard coat is applied decreases, resulting in a problem of reduced surface protection function for displays. In addition, lowering the refractive index in one direction improves deformation when folded, but increases uniaxial orientation in the folding direction, resulting in problems such as cracks or breakage at the folded portion. [Prior art documents] [Patent documents]

[0009] [Patent Document 1] JP 2010-228391 A [Patent Document 2] JP 2016-155124 A [Patent Document 3] International Publication No. 2018 / 150940 Summary of the Invention [Problem to be solved by the invention]

[0010] The present invention seeks to solve the problems associated with conventional display components as described above, and aims to provide a foldable display that is easy to mass-produce and has no risk of image distortion at the folded portion after repeated folding, and a polyester film for foldable displays that does not produce fold marks or cracks at the folded portion, in order to provide a mobile terminal device equipped with such a foldable display. [Means for solving the problem]

[0011] That is, the present invention comprises the following: 1. A polyester film for folding displays having a thickness of 10 to 80 μm and satisfying the following conditions: (1) The refractive index in the bending direction is 1.590 to 1.620 (2) The refractive index in the direction of the fold is 1.670 to 1.700 (3) Refractive index in the thickness direction is 1.520 or less (4) Density is 1.380 g / cm 3 End (Here, the bending direction refers to the direction perpendicular to the fold when folding the polyester film.) 2. The polyester film for folding displays according to claim 1, having a total light transmittance of 85% or more, a haze of 3% or less, and a maximum heat shrinkage rate of 6% or less. 3. The polyester film for folding displays according to claim 1 or 2, which has an easy-adhesion layer on at least one surface of the polyester film. 4. The polyester film for folding displays according to any one of the above 1 to 3, having an in-plane retardation (Re) of 3,000 to 30,000 nm. 5. A hard coat film for a foldable display, comprising the polyester film for a foldable display according to any one of the above 1 to 4, and a hard coat layer having a thickness of 1 to 50 μm on at least one surface of the polyester film for a foldable display. 6. A foldable display in which the hard coat film for a foldable display according to 5 above is arranged as a surface protective film so that the hard coat layer is positioned on the surface, and a continuous single hard coat film is arranged through the folding portion of the foldable display. 7. A mobile terminal device having the foldable display described in claim 6. Effect of the Invention

[0012] A foldable display using the polyester film for foldable displays or the hard coat film of the present invention maintains mass productivity, and the polyester film does not crack at the folding portion, does not deform after repeated folding, and does not cause image distortion at the folding portion of the display. A mobile terminal device equipped with a foldable display using the polyester film or hard coat film as described above provides beautiful images, is highly functional, and has excellent convenience such as portability. [Brief description of the drawings]

[0013] [Figure 1] FIG. 2 is a schematic diagram showing the bending radius when the foldable display of the present invention is folded. [Diagram 2] FIG. 2 is a schematic diagram showing the bending direction of the polyester film for folding displays according to the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] (display) The display in the present invention generally refers to a display device, and the types of displays include LCD, organic EL display, inorganic EL display, LED, FED, etc., but LCD, organic EL, and inorganic EL having a bendable structure are preferred. In particular, organic EL and inorganic EL, which can reduce the layer structure, are more preferred, and organic EL, which has a wide color gamut, is even more preferred.

[0015] (Foldable display) A folding display is a single continuous display that can be folded in half or the like when carried. By folding, the size can be halved, improving portability. The bending radius of a folding display is preferably 5 mm or less, and more preferably 3 mm or less. If the bending radius is 5 mm or less, it can be made thin when folded. It can be said that the smaller the bending radius, the better, but the smaller the bending radius, the more likely it is to leave creases. The bending radius is preferably 0.1 mm or more, but may be 0.5 mm or more, or may be 1 mm or more. Even if the bending radius is 1 mm, it is possible to achieve a practically sufficient thinness when carried. The bending radius when folded is measured at the location of the symbol 11 in the schematic diagram of FIG. 1, and means the radius of the inside of the folded part when folded. The surface protective film described later may be located on the outside or inside of the folded folding display. Furthermore, the foldable display may be folded in three or four, or may be a rollable type, all of which are considered to fall within the scope of the foldable display of the present invention.

[0016] The polyester film for folding displays of the present invention may be used in any part of a folding display as long as it is a component of the folding display. Below, a typical configuration of a folding display and the part in which the polyester film of the present invention can be used are described using an organic EL display as an example. Hereinafter, the polyester film for folding displays of the present invention may be simply referred to as the polyester film of the present invention.

[0017] (Foldable OLED display) The essential component of a folding organic EL display is an organic EL module, and further includes a circular polarizing plate, a touch panel module, a front protective film, a back protective film, and the like, as required. (Organic LED module) A typical structure of an organic EL module is an electrode / electron transport layer / light-emitting layer / hole transport layer / transparent electrode. The polyester film of the present invention can be used as a substrate on which an electrode is provided and an electron transport layer, a light-emitting layer, and a hole transport layer are further provided. In particular, it can be preferably used as a substrate for a transparent electrode. In this case, since the substrate film is required to have high barrier properties against water vapor and oxygen, it is preferable that the polyester film of the present invention is provided with a barrier layer such as a metal oxide layer. In order to improve the barrier properties, a plurality of barrier layers may be provided, or a plurality of polyester films provided with a barrier layer may be used.

[0018] (Touch panel module) It is preferable that the mobile terminal device has a touch panel. When an organic EL display is used, it is preferable that a touch panel module is disposed on the top of the organic EL display or between the organic EL module and the circular polarizer. The touch panel module has a transparent substrate such as a film and a transparent electrode disposed thereon. The polyester film of the present invention can be used as this transparent substrate. When used as a transparent substrate for a touch panel, it is preferable that the polyester film is provided with a hard coat layer or a refractive index adjustment layer.

[0019] (Circular polarizing plate) The circular polarizing plate suppresses deterioration of image quality due to reflection of external light by members inside the display. The circular polarizing plate has a linear polarizing plate and a retardation plate. The linear polarizing plate has a protective film on at least the viewing side surface of the polarizer. The polarizer may also have a protective film on the surface opposite to the viewing side, or the retardation plate may be directly laminated on the polarizer. The retardation plate is a resin film having a retardation such as polycarbonate or cyclic olefin, or a resin film provided with a retardation layer made of a liquid crystal compound. The polyester film of the present invention can be used as a polarizer protective film or a resin film for a retardation plate. In these cases, it is preferable that the slow axis direction of the polyester film of the present invention is parallel or perpendicular to the absorption axis direction of the polarizer. Incidentally, a deviation of 10 degrees, preferably 5 degrees, from this parallel or perpendicular direction is allowed.

[0020] (Surface protection film) When an impact is applied to a display from above, the circuit of an organic EL module or a touch panel module may be broken, so a surface protective film is often provided. The polyester film of the present invention is used as this surface protective film. Surface protective films include those called cover windows that are incorporated into the outermost surface of a display, and those called afters that can be attached, peeled off, and replaced by the user himself, but the polyester film of the present invention is used in either case. When the polyester film of the present invention is used as a surface protective film, it is preferable that a hard coat layer is laminated on at least the surface side of the polyester film. The hard coat layer is provided on the surface of a folding display with the hard coat layer on the viewing side. The hard coat layer may be provided on both sides.

[0021] (Back protection film) It is also preferable that a protective film is provided on the back side of the display, and the polyester film of the present invention can be used as the protective film on the back side.

[0022] The polyester film of the present invention may be any other film than those described above, so long as it is used in a portion that is folded as a component of a folding display. Among these, the polyester film of the present invention is preferably used as a cover window surface protection film, an after-surface protection film, a base film of a touch panel module, or a back surface protection film, and more preferably used as a cover window surface protection film or an after-surface protection film.

[0023] In addition, it is not necessary for the polyester film of the present invention to be used in all of the above-mentioned foldable displays. In addition to the polyester film of the present invention, polyimide films, polyamide films, polyamideimide films, polyester films other than the polyester film of the present invention, polycarbonate films, acrylic films, triacetyl cellulose films, cycloolefin polymer films, polyphenylene sulfide films, polymethylpentene films, and the like can be used in foldable displays according to their suitability.

[0024] The polyester film of the present invention may be a single-layer film made of one or more types of polyester resin, or when two or more types of polyester are used, it may be a multilayer film or an ultra-multilayer laminate film having a repeating structure.

[0025] Examples of polyester resins used in the polyester film include polyester films made of polyethylene terephthalate, polybutylene terephthalate, polyethylene-2,6-naphthalate, or copolymers mainly made of these resin components. Among these, stretched polyethylene terephthalate films are particularly preferred in terms of mechanical properties, heat resistance, transparency, price, etc.

[0026] When a polyester copolymer is used for the polyester film, examples of the dicarboxylic acid component of the polyester include aliphatic dicarboxylic acids such as adipic acid and sebacic acid; aromatic dicarboxylic acids such as terephthalic acid, isophthalic acid, phthalic acid, and 2,6-naphthalenedicarboxylic acid; and polyfunctional carboxylic acids such as trimellitic acid and pyromellitic acid. Examples of the glycol component include fatty acid glycols such as ethylene glycol, diethylene glycol, 1,4-butanediol, propylene glycol, and neopentyl glycol; aromatic glycols such as p-xylene glycol; alicyclic glycols such as 1,4-cyclohexanedimethanol; and polyethylene glycols having an average molecular weight of 150 to 20,000. The mass ratio of the copolymerization components of the preferred copolymer is less than 20% by mass. When it is less than 20% by mass, the film strength, transparency, and heat resistance are maintained, which is preferable.

[0027] In addition, in the production of polyester film, the intrinsic viscosity of at least one type of resin pellet is preferably in the range of 0.50 to 1.0 dl / g. When the intrinsic viscosity is 0.50 dl / g or more, the impact resistance of the obtained film is improved, and disconnection of the internal circuit of the display due to external impact is less likely to occur, which is preferable. On the other hand, when the intrinsic viscosity is 1.00 dl / g or less, the increase in filtration pressure of the molten fluid is not too large, and film production can be easily and stably operated, which is preferable.

[0028] The thickness of the polyester film is preferably 10 to 80 μm, and more preferably 25 to 75 μm. A thickness of 10 μm or more improves the pencil hardness and impact resistance, while a thickness of 80 μm or less is advantageous for weight reduction and is excellent in flexibility, processability, handleability, and the like.

[0029] The surface of the polyester film of the present invention may be smooth or uneven, but since it is used for display surface covering, the deterioration of optical properties due to unevenness is not preferable. The haze is preferably 3% or less, more preferably 2% or less, and most preferably 1% or less. If the haze is 3% or less, the visibility of the image can be improved. The lower limit of the haze is preferably 0.1% or more from the viewpoint of stable production, but it may be 0.3% or more.

[0030] As described above, in order to reduce haze, it is preferable that the unevenness of the film surface is not too large. However, in order to provide a certain degree of slipperiness from the viewpoint of ease of handling, unevenness can be formed by blending particles into the surface polyester resin layer or by coating a coating layer containing particles during the film formation process.

[0031] The method of blending the particles in the polyester resin layer can be a known method. For example, it can be added at any stage of polyester production, but preferably it can be added as a slurry dispersed in ethylene glycol or the like at the stage of esterification, or after the completion of the transesterification reaction, and before the start of the polycondensation reaction, to proceed with the polycondensation reaction. It can also be performed by using a vented kneading extruder to blend the slurry of particles dispersed in ethylene glycol or water with the polyester raw material, or by using a kneading extruder to blend the dried particles with the polyester raw material.

[0032] Among them, a method is preferred in which aggregated inorganic particles are homogeneously dispersed in a monomer liquid that will become a part of the polyester raw material, and then the filtered product is added to the remainder of the polyester raw material before, during, or after the esterification reaction. According to this method, since the monomer liquid has a low viscosity, homogeneous dispersion of the particles and highly accurate filtration of the slurry can be easily performed, and when added to the remainder of the raw material, the dispersibility of the particles is good and new aggregates are unlikely to be generated. From this viewpoint, it is particularly preferred to add to the remainder of the raw material in a low temperature state before the esterification reaction.

[0033] In addition, the number of protrusions on the film surface can be further reduced by a method in which, after obtaining a polyester containing particles in advance, the pellets are mixed and extruded with pellets not containing particles (master batch method).

[0034] The polyester film may contain various additives, such as antistatic agents, UV absorbers, and stabilizers, within a range that maintains the total light transmittance in a preferred range.

[0035] The total light transmittance of the polyester film is preferably 85% or more, and more preferably 87% or more. With a transmittance of 85% or more, sufficient visibility can be ensured. The higher the total light transmittance of the polyester film, the better, but from the viewpoint of stable production, it is preferably 99% or less, and may be 97% or less.

[0036] The maximum heat shrinkage of the polyester film after heat treatment at 150°C for 30 minutes is preferably 6% or less, more preferably 5% or less. If the heat shrinkage is 6% or less, flatness defects such as curling and waviness during HC processing can be suppressed. The lower the heat shrinkage, the better, but it is preferably -1% or more, and more preferably 0% or more. The negative value here means that the film expanded after heating, and flatness defects may occur if the value is less than -1%.

[0037] The polyester film for folding displays of the present invention can provide sufficient pencil hardness to the hard coat film after laminating the hard coat layer. It is considered that the pencil hardness of the conventional polyester film is reduced in the pencil hardness evaluation of the hard coat film after laminating the hard coat layer due to the film being deformed in the thickness direction. In the present invention, by setting the indentation depth after unloading the test force in the film thickness direction using a dynamic ultra-micro hardness tester described later to a specific range, a high hardness can be achieved in the pencil hardness evaluation of the hard coat film. The indentation depth after unloading the test force in the film thickness direction is preferably 1.5 μm or less, more preferably 1.4 μm or less, and even more preferably 1.3 μm or less. If the indentation depth after unloading the test force (final deformation amount when a load is applied) is 1.5 μm or less, the film is less likely to deform in the thickness direction in the pencil hardness evaluation of the hard coat film after laminating the hard coat layer, and the pencil hardness can be increased. If the pencil hardness of the hard coat film can be increased, scratches and dents are less likely to occur on the display surface, improving the visibility of the display. The lower the indentation depth after the test force is removed, the better, but from the viewpoints of stable production and saturation of the effect, a depth of 0.3 μm or more is preferable, and even more preferable is 0.5 μm or more.

[0038] In order to reduce the indentation depth after the test force is removed, it is effective to adjust the refractive index in the thickness direction to 1.520 or less. As a means for adjusting the refractive index to 1.520 or less, as described later, examples of the means include setting conditions such as adjusting the stretch ratio in the bending direction or folding direction to a high value, setting the stretching temperature in the bending direction or folding direction to a low value, and setting the heat setting temperature to a high value, within a range in which other physical properties and the refractive index in the bending direction or folding direction can be controlled to a preferred range.

[0039] The surface of the polyester film of the present invention may be subjected to a treatment for improving adhesion to a resin forming a hard coat layer or the like.

[0040] Examples of the surface treatment method include roughening treatment using sandblasting or solvent treatment, and oxidation treatment such as corona discharge treatment, electron beam irradiation treatment, plasma treatment, ozone or ultraviolet irradiation treatment, flame treatment, chromic acid treatment, or hot air treatment, and any of these methods can be used without any particular limitation.

[0041] In addition, the adhesion can be improved by an adhesion improving layer such as an easy-adhesion layer. The easy-adhesion layer can be made of any resin such as an acrylic resin, a polyester resin, a polyurethane resin, or a polyether resin, and can be formed by a general coating method, preferably a so-called in-line coating method.

[0042] The polyester film described above can be produced, for example, through a polymerization step in which inorganic particles are homogeneously dispersed in a monomer liquid that becomes a part of the polyester raw material, the dispersion is filtered, and then the dispersion is added to the remainder of the polyester raw material to polymerize the polyester, and a film formation step in which the polyester is melt-extruded through a filter into a sheet, which is cooled and stretched to form a base film.

[0043] Next, a method for producing a biaxially stretched polyester film will be described in detail using an example in which polyethylene terephthalate (hereinafter, sometimes referred to as PET) pellets are used as the raw material for the base film, but the present invention is not limited to this example. In addition, the number of layers is not limited to a single layer or a multilayer structure.

[0044] After mixing and drying PET pellets in a predetermined ratio, the mixture is fed to a known melt lamination extruder, extruded from a slit die into a sheet, and cooled and solidified on a casting roll to form an unstretched film. In the case of a single layer, one extruder is sufficient, but in the case of producing a film with a multilayer structure, two or more extruders, two or more manifolds or merging blocks (e.g., merging blocks having a rectangular merging portion) are used to laminate multiple film layers constituting each outermost layer, and a sheet of two or more layers is extruded from a die and cooled on a casting roll to form an unstretched film.

[0045] In this case, it is preferable to perform high-precision filtration to remove foreign matter contained in the resin at any location where the molten resin is kept at about 280° C. during melt extrusion. The filter material used for high-precision filtration of the molten resin is not particularly limited, but a filter material made of sintered stainless steel is preferable because it has excellent performance in removing aggregates and high-melting organic matter mainly composed of Si, Ti, Sb, Ge, and Cu.

[0046] Furthermore, the filtration particle size (initial filtration efficiency 95%) of the filter medium is preferably 20 μm or less, particularly preferably 15 μm or less. If the filtration particle size (initial filtration efficiency 95%) of the filter medium exceeds 20 μm, foreign matter with a size of 20 μm or more cannot be sufficiently removed. By using a filter medium with a filtration particle size (initial filtration efficiency 95%) of 20 μm or less to perform high-precision filtration of molten resin, productivity may decrease, but it is preferable to obtain a film with few protrusions due to coarse particles.

[0047] (Refractive index in bending direction) In the present invention, the refractive index of at least one of the longitudinal direction (machine flow direction) and the width direction of the polyester film is preferably 1.590 to 1.620, more preferably 1.591 to 1.600. The refractive index of the bending direction of the polyester film is preferably 1.590 to 1.620, more preferably 1.591 to 1.600. Here, the bending direction refers to the direction perpendicular to the folding part (reference number 21) assumed in the use of a folding display, as shown by reference number 22 on the polyester film (reference number 2) in FIG. 2. When the refractive index of at least one of the longitudinal direction and the width direction is 1.590 to 1.620, there is little deformation when repeatedly folded, and there is no risk of deteriorating the image quality of the folding display, which is preferable. The refractive index is more preferably 1.591 to 1.600. Of course, the direction is preferably the bending direction. If the refractive index is 1.590 or more, there is no risk of cracks occurring in the folded portion direction after the bending test described below, and of course no breakage occurs, so that the visibility of the display can be maintained good. The refractive index of the polyester film can be effectively adjusted by adjusting the stretching ratio and stretching temperature. In addition, a relaxation process in the stretching direction and multi-stage stretching may be used to adjust the refractive index. When multi-stage stretching is performed, it is preferable to make the stretching ratios in the second and subsequent stages higher than the stretching ratio in the first stage.

[0048] By controlling the refractive index in at least one of the longitudinal direction (machine flow direction) and the width direction of the polyester film within the above range, and more preferably by controlling the refractive index in the bending direction within the above range, fatigue due to the compressive stress applied to the inside of the fold when folded can be reduced. It is believed that fatigue due to compressive stress occurs mainly in the crystalline portion, and fatigue is less likely to occur when there are fewer crystals in the bending direction. Therefore, it is believed that by lowering the refractive index, the amount of oriented crystals in the bending direction is reduced, and compression fatigue is suppressed.

[0049] Furthermore, the creep phenomenon caused by tensile stress applied to the outside of the fold when the material is folded can be suppressed by reducing the refractive index. Fatigue caused by tensile stress is thought to occur mainly in the amorphous portion, and the repeated application of stress causes molecular chains to align, resulting in deformation. It can be assumed that the fewer molecular chains aligned in the bending direction, the less deformation caused by alignment. Furthermore, since fatigue caused by tension can be suppressed with fewer amorphous portions, a higher degree of crystallinity, i.e., a higher density, is preferable.

[0050] In the present invention, the stretching ratio of the unstretched polyester sheet in at least one of the longitudinal direction (machine flow direction) and the width direction is preferably 1.2 to 2.0 times, more preferably 1.7 to 2.0 times. The stretching direction is preferably the bending direction. A stretching ratio of 1.2 times or more is preferable because there is no deformation during post-processing such as hard coat coating, and a stretching ratio of 2.0 times or less is preferable because thickness unevenness of the film does not occur. The stretching temperature is preferably 75 to 120°C, more preferably 75 to 105°C. The heating method during stretching can be a conventionally known method such as hot air heating method, roll heating method, and infrared heating method. By setting the stretching temperature to 75 to 120°C, it is possible to prevent large thickness unevenness due to stretching at the above stretching ratio. In addition, by stretching at a temperature as low as possible within a range in which large thickness unevenness does not occur as described above, the refractive index in the thickness direction can be reduced.

[0051] (Refractive index in the direction of the fold) The refractive index of the polyester film in the direction perpendicular to the direction in which the refractive index is 1.590 to 1.620 is preferably 1.670 to 1.700. That is, the refractive index in the direction perpendicular to the bending direction (direction of the folded portion) is preferably 1.670 to 1.700. By making it 1.670 to 1.700, deformation when folded in the bending direction can be reduced. By making it 1.700 or less, cracks and breaks in the direction of the folded portion can be suppressed. By making it 1.670 or more, the flexibility in the bending direction can be improved and the surface hardness can be improved. 1.680 to 1.695 is more preferable. Methods for adjusting the refractive index in the direction perpendicular to the bending direction include the stretching ratio, stretching preheating temperature, stretching temperature, multi-stage stretching, and film relaxation. The stretching ratio is preferably 4.0 to 6.0 times, more preferably 4.4 to 6.0 times. In addition, the stretching preheating temperature in the direction perpendicular to the bending direction is preferably 70 to 110°C. When multi-stage stretching is performed in a direction perpendicular to the bending direction, it is preferable to set the stretching ratio higher in the second and subsequent stages than in the first stage. The film may be relaxed by 1 to 10% in either the machine flow direction (longitudinal direction) or the perpendicular direction (width direction).

[0052] (Refractive index in the thickness direction) The refractive index in the thickness direction is preferably 1.520 or less. By setting the refractive index to 1.520 or less, even if the refractive index in the bending direction is designed to be low, the decrease in hardness of the film surface can be suppressed, and both flexibility and surface hardness can be achieved. By setting the refractive index to 1.520 or less, the indentation depth after unloading the test force in the thickness direction is reduced, and the hardness of the film surface, particularly the pencil hardness of the hard coat film after lamination of the hard coat layer, can be improved. More preferably, it is 1.515 or less, even more preferably 1.510 or less, particularly preferably 1.505 or less, and most preferably 1.500 or less. The refractive index in the thickness direction is preferably low, but from the viewpoint of stable production, it is preferably 1.3 or more, and may even be 1.4 or more. Particularly preferably, it is 1.410 or more. It can be said that the above range can be achieved by increasing the stretch ratio in both the bending direction and the folding direction, but in order to control the refractive index in the thickness direction after controlling the refractive index in the bending direction and the width direction to a preferred range, it is preferable to set the conditions while checking the balance of the conditions of each process in the film formation process.

[0053] The method of controlling the refractive index in the thickness direction to the above range includes the preheating temperature, stretching temperature, and stretching ratio in the bending direction, the preheating temperature, stretching temperature, multi-stage stretching, high-ratio stretching, or heat fixing temperature setting in the folding direction. The preheating temperature in the bending direction is preferably 70°C to 110°C. The stretching temperature in the bending direction is preferably 75°C to 120°C. The stretching ratio in the bending direction is preferably 1.2 to 2.0 times, more preferably 1.7 to 2.0 times. By lowering the stretching temperature and stretching at a low stretching ratio, the refractive index in the thickness direction can be effectively reduced while maintaining the flexibility in the bending direction. The preheating temperature in the folding direction is also preferably 75°C to 110°C. The stretching temperature is preferably 75°C to 120°C. The stretching ratio in the folding direction is preferably 4.0 to 6.0 times, more preferably 4.4 to 6.0 times. The refractive index in the thickness direction can be effectively reduced while maintaining or reducing the refractive index in the bending direction. Multi-stage stretching may be used as a method of high-ratio stretching. In this case, it is preferable to set the stretching ratio in the second stage higher than that in the first stage, since this allows for effective control of the refractive index. A method of stretching again after the crystallization step may also be used. Accelerated stretching, in which the stretching speed is increased from the initial stage to the latter stage of stretching, may also be used. The heat setting temperature is preferably 180 to 240° C. By carrying out heat setting, oriented crystallization in the stretching direction advances, and the refractive index in the thickness direction can be reduced. The reason why lowering the refractive index in the thickness direction improves the hardness of the film surface is not entirely clear, but it is thought that aromatic groups such as benzene rings in the molecular chain are oriented in the plane direction, which has the effect of suppressing deformation due to stress applied in the thickness direction.

[0054] (Regarding density of polyester film) The density of polyester film is 1.380g / cm 3 It is preferable that the density is 1.383 g / cm or more. 3 More preferably, it is 1.380 g / cm or more. 3By setting the density to 1.40 g / cm or more, it is possible to improve the flexibility and the film surface hardness, particularly the pencil hardness of the hard coat film after laminating the hard coat layer. The higher the density, the better. Although it depends somewhat on the presence or absence of particles in the film, it is preferable to set the density to 1.40 g / cm or more. 3 It is preferable that the density is 1.395 g / cm or less, and more preferably 1.395 g / cm 3 The following is more preferable. By setting the heat setting temperature during film formation to 180 to 240°C, crystallization can be promoted and the density can be effectively increased. 3 Below this temperature, crystallization is insufficient, which makes the film more susceptible to deformation due to bending, and the thermal shrinkage rate increases, which makes it difficult to process the film when applying a hard coat.

[0055] The bending direction of the polyester film is preferably set to correspond to the longitudinal direction (machine flow direction). This makes it easier to reduce the refractive index in the bending direction by biaxial stretching and improve the flexibility. That is, a polyester film is preferably obtained by stretching an unstretched polyester sheet in the longitudinal direction at a stretching ratio of 1.2 to 2.0 times, more preferably 1.7 to 2.0 times. In addition, it can be said that a preferred embodiment is to stretch the polyester sheet in the transverse direction at a stretching ratio of 4.0 to 6.0 times, more preferably 4.4 to 6.0 times.

[0056] In the present invention, the polyester film (1) The refractive index in the bending direction is 1.590 to 1.620 (2) The refractive index in the direction of the fold is 1.670 to 1.700 (3) Refractive index in the thickness direction is 1.520 or less (4) Density is 1.380 g / cm 3 End It is particularly preferable to have the above four characteristics simultaneously, but even if the combination is within the above-mentioned preferred manufacturing conditions, it may not necessarily be possible to obtain a film that satisfies all four characteristics simultaneously if the combination is not the best within each preferred manufacturing condition range, for example, a combination of a stretch ratio in the bending direction of 1.4 times or less, a stretch ratio in the folding direction of less than 4.4 times, and a heat setting temperature of 220° C. or less. In this case, the above four characteristics can be simultaneously satisfied by fine-tuning any of the conditions or a combination of them, such as increasing the stretch ratio in the bending direction to 1.7 times or more, increasing the stretch ratio in the folding direction to 4.4 times or more, increasing the heat setting temperature to about 230° C., or lowering the stretching temperature in the bending direction and / or the folding direction.

[0057] In order to adjust the film formability, film strength, thermal dimensional stability, and appearance defects, any film forming method such as stretching, relaxation, heat setting, and surface treatment may be used, but it can be said that a particularly preferred embodiment of the present invention is to control the refractive index and density of the film within the above-mentioned preferred ranges. By controlling the refractive index and density within the preferred ranges, it is possible to provide a polyester film suitable for a folding display, which has superior flex resistance and surface hardness compared to conventional films, particularly high pencil hardness of the hard coat film after laminating a hard coat layer.

[0058] Specifically, for example, PET pellets are thoroughly vacuum-dried, then fed to an extruder, melt-extruded into a sheet at about 280°C, and cooled and solidified to form an unstretched PET sheet. The unstretched sheet obtained is stretched 1.2 to 2.0 times, more preferably 1.7 to 2.0 times, in the longitudinal direction with a roll heated to 75 to 120°C to obtain a uniaxially oriented PET film. Furthermore, the end of the film is held by a clip and introduced into a hot air zone heated to 75 to 120°C, and after drying, is stretched 4.0 to 6.0 times, more preferably 4.4 to 6.0 times, in the transverse direction. Subsequently, the film can be introduced into a heat treatment zone at 180 to 240°C and heat-treated for 1 to 60 seconds. During this heat treatment process, a relaxation treatment of 0 to 10% may be performed in the transverse or longitudinal direction as necessary.

[0059] The intrinsic viscosity of the polyester film is preferably in the range of 0.50 to 1.0 dl / g. When the intrinsic viscosity is 0.50 dl / g or more, the impact resistance is improved and disconnection of the internal circuit of the display due to external impact is less likely to occur, which is preferable. On the other hand, when the intrinsic viscosity is 1.00 dl / g or less, the increase in the filtration pressure of the molten fluid is not too large, which is preferable because film production is stable.

[0060] When a birefringent polymer film is placed on the viewing side of the display module and observed from an oblique direction, coloring or rainbow-like color spots (iridescence) may occur. This is because a part of the light emitted from the display module is reflected at the interface to generate a polarized component, and when this polarized component passes through the polyester film, it is converted into linear circular light or elliptically polarized light perpendicular to the original polarized light by the in-plane retardation (Re), which is the product of the birefringence and thickness of the polymer film, and some of the polarized components of this converted polarized light are removed by reflection at the film-air interface, etc. This coloring and rainbow spots can be prevented by making the in-plane retardation (Re) of the polyester film 3000 nm or more. This is because the pattern converted into linear circular light or elliptically polarized light depends on the wavelength and in-plane retardation (Re), but by increasing the in-plane retardation (Re), this pattern can be repeated at a short wavelength period, and as a result, the envelope shape of the spectrum of the transmitted light can be made to approximate the emission spectrum of the light source, making it indistinguishable to the human eye.

[0061] A preferable lower limit of the in-plane retardation (Re) is 4500 nm, and a more preferable lower limit is 6000 nm.

[0062] On the other hand, from the viewpoint of the visibility (suppression of rainbow spots), the upper limit of the in-plane retardation (Re) is preferably 30,000 nm. The upper limit of the in-plane retardation (Re) is more preferably 20,000 nm, further preferably 15,000 nm, particularly preferably 12,000 nm, and most preferably 10,000 nm.

[0063] The in-plane retardation (Re) of the polyester film in the present invention can be determined by measuring the refractive index in two axial directions and the thickness, or by using a commercially available automatic birefringence measuring device such as KOBRA-21ADH (Oji Scientific Instruments Co., Ltd.). The slow axis direction can be determined by using a molecular orientation meter (for example, MOA-6004 type molecular orientation meter manufactured by Oji Scientific Instruments Co., Ltd.).

[0064] Since the OLED light source used in foldable displays has a wide emission spectrum, by setting the in-plane retardation (Re) of the polyester film within the above range, it is possible to approximate the envelope shape of the transmitted light spectrum to the emission spectrum of the light source with only a relatively simple configuration.

[0065] When a polarizing plate is present on the viewing side of a display module, the polyester film of the present invention is preferably disposed on the viewing side of the polarizing plate, which is preferable because it not only improves visibility but also provides sufficient antireflection function.

[0066] There is no particular limitation on the angle between the absorption axis of the polarizing plate and the slow axis of the polymer film, but from the viewpoint of convenience in cutting out the polarizing plate and the polymer film, the angle between the absorption axis of the polarizing plate and the slow axis of the polymer film is preferably 0 degrees or 90 degrees. Furthermore, from the viewpoint of easily reducing coloring and rainbow spots even when the in-plane retardation (Re) is relatively low, the angle between the absorption axis of the polarizing plate and the slow axis of the polymer film is preferably 0 degrees. In this case, it is preferable that the range of ±20 degrees, and even ±10 degrees, is allowed with respect to 0 degrees or 90 degrees. On the other hand, from the viewpoint of preventing blackout when viewing a screen through polarized sunglasses, it is preferable that the angle is more than 20 degrees and less than 70 degrees, and more preferably 30 degrees to 60 degrees.

[0067] (Easy adhesion layer) In the present invention, in order to improve the adhesion between the polyester film and the hard coat layer, etc., it is also preferable to laminate an easy-adhesion layer on the polyester film. The easy-adhesion layer can be obtained by applying a coating liquid for forming the easy-adhesion layer to one or both sides of an unstretched or uniaxially stretched film in the longitudinal direction, heat-treating and drying as necessary, and then stretching the film in at least one direction that is not stretched. Heat treatment can also be performed after biaxial stretching. The final coating amount of the easy-adhesion layer is 0.005 to 0.20 g / m 2 It is preferable to control the coating amount to 0.005 g / m 2 On the other hand, if the coating amount is 0.20 g / m or more, adhesiveness is obtained, which is preferable. 2If it is not more than this, blocking resistance can be obtained, which is preferable.

[0068] Resins contained in the coating liquid used for laminating the easy-adhesion layer can be, for example, polyester resins, polyether polyurethane resins, polyester polyurethane resins, polycarbonate polyurethane resins, acrylic resins, etc., and can be used without particular limitation. Examples of crosslinking agents contained in the coating liquid for forming the easy-adhesion layer include melamine compounds, isocyanate compounds, oxazoline compounds, epoxy compounds, carbodiimide compounds, etc. Two or more of each can also be mixed and used. Due to the nature of in-line coating, these are preferably applied using a water-based coating liquid, and the resins and crosslinking agents are preferably water-soluble or water-dispersible resins or compounds.

[0069] It is preferable to add particles to the easy-adhesion layer to give it easy slipperiness. The average particle size of the fine particles is preferably 2 μm or less. If the average particle size of the particles exceeds 2 μm, the particles are likely to fall off from the easy-adhesion layer. Examples of particles to be contained in the easy-adhesion layer include inorganic particles such as titanium oxide, barium sulfate, calcium carbonate, calcium sulfate, silica, alumina, talc, kaolin, clay, calcium phosphate, mica, hectorite, zirconia, tungsten oxide, lithium fluoride, and calcium fluoride, and organic polymer particles such as styrene-based, acrylic-based, melamine-based, benzoguanamine-based, and silicone-based particles. These may be added to the easy-adhesion layer alone, or two or more types may be added in combination.

[0070] The coating liquid can be applied by a known method, similar to the coating layer described above, such as reverse roll coating, gravure coating, kiss coating, roll brushing, spray coating, air knife coating, wire bar coating, and pipe doctor coating, which can be used alone or in combination.

[0071] (Hard coat layer) When the polyester film of the present invention is used as a surface protection film for protecting a folding display by placing it on the surface of the display, it is preferable that the polyester film has a hard coat layer on at least one surface. The hard coat layer is preferably placed on the display surface side of the polyester film and used in the display. The resin for forming the hard coat layer can be any of acrylic, siloxane, inorganic hybrid, urethane acrylate, polyester acrylate, epoxy, and other resins without any particular limitation. Two or more materials can be mixed and used, or particles such as inorganic filler or organic filler can be added.

[0072] (Thickness of hard coat layer) The thickness of the hard coat layer is preferably 1 to 50 μm. If the thickness is 1 μm or more, it is preferable because it is cured sufficiently and has a high pencil hardness. Furthermore, if the thickness is 50 μm or less, curling due to cure shrinkage of the hard coat can be suppressed, and the handling properties of the film can be improved.

[0073] (Application method) The hard coat layer can be applied by any method including, but not limited to, a Mayer bar, a gravure coater, a die coater, a knife coater, etc., and can be appropriately selected depending on the viscosity and film thickness.

[0074] (Curing conditions) The hard coat layer can be cured by energy rays such as ultraviolet rays and electron beams, or by heat, and is preferably cured by ultraviolet rays or electron beams in order to reduce damage to the film.

[0075] (Pencil hardness) The pencil hardness of the hard coat layer is preferably 3H or more, more preferably 4H or more. If the hard coat layer has a pencil hardness of 3H or more, it is not easily scratched and does not reduce visibility. In general, the pencil hardness of the hard coat layer is preferably high, but it may be 9H or less, 8H or less, or even 6H or less can be used without any practical problems.

[0076] (Characteristics of hard coat layer) The hard coat layer in the present invention can be used for the purpose of protecting a display by increasing the pencil hardness of the surface as described above, and preferably has a high transmittance. The total light transmittance of the hard coat film is preferably 87% or more, more preferably 88% or more. If the transmittance is 87% or more, sufficient visibility can be obtained. The total light transmittance of the hard coat film is generally the higher the better, but from the viewpoint of stable production, it is preferably 99% or less, and may be 97% or less. In addition, the haze of the hard coat film is generally preferably low, and preferably 3% or less. The haze of the hard coat film is more preferably 2% or less, and most preferably 1% or less. If the haze is 3% or less, the visibility of the image can be improved. The lower the haze, the better, but from the viewpoint of stable production, it is preferably 0.1% or more, and may be 0.3% or more.

[0077] The hard coat layer may further have other functions added thereto. For example, a hard coat layer having the above-mentioned functions such as an antiglare layer having a certain pencil hardness, an antiglare antireflection layer, an antireflection layer, a low reflection layer, and an antistatic layer is preferably used in the present invention.

[0078] A hard coat layer may also be provided when used as a substrate film of a touch panel module. When an ITO layer is used as a transparent electrode layer of a touch panel module, for example, a refractive index adjustment layer is preferably provided between the substrate film and the transparent electrode layer to make the electrode pattern less visible. In this case, the hard coat layer itself may also serve as a refractive index adjustment layer, or a separate layer for refractive index adjustment may be laminated. EXAMPLES

[0079] Next, the present invention will be described with reference to examples and comparative examples. First, the evaluation methods of the characteristic values ​​carried out in the present invention will be described below.

[0080] (1) Intrinsic viscosity The film or polyester resin was crushed and dried, and then dissolved in a mixed solvent of phenol / tetrachloroethane = 60 / 40 (mass ratio). After the solution was centrifuged to remove inorganic particles, the flow time of the solution with a concentration of 0.4 (g / dl) at 30°C and the flow time of the solvent alone were measured using an Ubbelohde viscometer, and the intrinsic viscosity was calculated from the ratio of these times using the Huggins equation and assuming that the Huggins constant is 0.38.

[0081] (2) Bending resistance of polyester film sample (bending radius 1.5 mm) A polyester film sample with a size of 20 mm in the width direction × 110 mm in the flow direction is prepared. Using a no-load U-shaped stretch tester (Yuasa System Co., Ltd., DLDMLH-FS), the bending radius is set to 1.5 mm, and the sample is bent 200,000 times at a speed of 1 time / second. At that time, the sample is fixed at a position 10 mm from both ends of the long side, and the bending portion is 20 mm × 90 mm. Here, FIG. 1 is a schematic diagram for showing the bending radius when a folding display is folded, and considering the case where a polyester film is arranged on the inner surface of the folded state, a bending test is performed as a model with the portion indicated by the symbol 11 in FIG. 1 set to 1.5 mm. After the bending process, the sample was placed on a flat surface with the inner side of the bend facing down, and visual observation was performed. ○: No cracks or deformations were observed in the sample. ×: The sample had a crack or crease, and when placed horizontally, the maximum floating height was 5 mm or more.

[0082] (3) Bending resistance of polyester film sample (bending radius 0.5 mm) In the same manner as in the bending test, the bending radius was set to 0.5 mm and the display was bent 200,000 times at a speed of 1 time / second. Here, FIG. 1 is a schematic diagram showing the bending radius when the foldable display is folded, and considering the case where a polyester film is arranged on the inner surface of the folded state, a bending test was performed as a model with the portion indicated by reference numeral 11 in FIG. 1 set to 0.5 mm. The film surface on the outer side of the bent portion was observed at 700 times magnification with a digital microscope (HIROX RH8800) to observe the presence or absence of wrinkles (cracks). In addition to the above-mentioned visual bending resistance test with a bending radius of 1.5 mm, this test was performed with the bending radius reduced to 0.5 mm, with the intention of evaluating the display in a state close to the actual use state of the foldable display in which a hard coat layer or other members are laminated or attached. In addition to the visual observation with a bending radius of 1.5 mm, this test is for detecting minute defects that are difficult to detect by visual inspection, such as defects that are prone to breakage or cracking. ○: No defects on the film surface on the outer side of the bend. ×: Broken or wrinkles (cracks) were observed on the film surface on the outer side of the bend.

[0083] (4) Refractive index In accordance with JIS K 7142:2008 "Measurement method for refractive index of plastics (Method A)", the refractive index in the longitudinal direction, width direction, and thickness direction were determined using an Abbe refractometer (Atago Co., Ltd., NAR-4T, measurement wavelength 589 nm).

[0084] (5) Pencil hardness The pencil hardness of the hard coat film was measured using a sample at a load of 750 g and a speed of 1.0 mm / s in accordance with JIS K 5600-5-4: 1999. In the present invention, a value of 3H or more was considered to be acceptable.

[0085] (6) Total light transmittance, haze The haze was measured using a haze meter (NDH5000, manufactured by Nippon Denshoku Industries Co., Ltd.).

[0086] (7) Density The density was measured according to the method compliant with JIS K 7112:1999 (density gradient tube method). (Unit: g / cm 3 ).

[0087] (8) Indentation depth after removing the test force The sample was cut into approximately 2 cm squares and fixed on a micro cover glass 18 × 18 mm (manufactured by Matsunami Glass Co., Ltd.) with an adhesive (Cemedine (registered trademark) High Super 30) on the surface opposite to the measurement surface. After adhesion and fixing, it was left at room temperature for 12 hours or more, and then the indentation depth (μm) after removing the test force was measured using a dynamic ultra-microhardness tester "DUH-211" (manufactured by Shimadzu Corporation) under the following conditions. <Measurement conditions> Test mode: Load-unload test Indenter used: Triangular pyramidal indenter with ridge angle of 115 degrees Indenter elastic modulus: 1.140×10 6 N / mm 2 Indenter Poisson's ratio: 0.07 Test force: 50mN Load speed: 4.44mN / sec Load holding time: 2sec Unloading holding time: 0sec

[0088] (9) Maximum heat shrinkage rate The sample film was cut to 10 mm length x 250 mm width, and marks were made at 200 mm intervals along the long side in the direction to be measured, and the distance A between the marks was measured under a constant tension of 5 g. The sample film was then left in an oven at 150°C for 30 minutes without load, and then removed from the oven and cooled to room temperature. The distance B between the marks was then measured under a constant tension of 5 g, and the thermal shrinkage rate (%) was calculated using the following formula. The thermal shrinkage rate was measured at three equal positions in the width direction of the sample film, and the average value of the three points was taken as the thermal shrinkage rate (%). Heat shrinkage rate (%) = [(AB) x 100] / A The sample film is cut so that the length and width of the sample differ in both the bending direction and the folding direction, and measurements are taken. The data in the direction where the measured value is greater is regarded as the maximum heat shrinkage rate (%).

[0089] (10) In-plane retardation (Re) It is a parameter defined by the product (ΔN×d) of the refractive index anisotropy of two orthogonal axes on a film (ΔN=|Nx-Ny|) and the film thickness d (nm), and is a measure of optical isotropy and anisotropy. The biaxial refractive index anisotropy (ΔN) is determined by the following method. Using two polarizing plates, the orientation axis direction of the film is determined, and a 4 cm×2 cm rectangle is cut out so that the orientation axis direction is perpendicular to the film, and used as a measurement sample. For this sample, the refractive indexes of the two orthogonal axes (Nx, Ny) and the refractive index in the thickness direction (Nz) are determined by an Abbe refractometer (Atago Co., Ltd., NAR-4T), and the absolute value of the difference in the refractive index of the two axes (|Nx-Ny|) is taken as the refractive index anisotropy (ΔN). The thickness d (nm) of the film was measured using an electric micrometer (Fine Leaf Co., Ltd., Millitron 1245D) and converted to nm. The in-plane retardation (Re) was calculated from the product (ΔN×d) of the refractive index anisotropy (ΔN) and the film thickness d (nm). Among the orientation axes, the axis showing a larger refractive index is defined as the slow axis.

[0090] (11) Iridescence observation The polyester film of the present invention was attached to the surface of an OLED tablet (Samsung Galaxy Tab S3 SM-T820 9.7-inch 32GB Tablet) using water, with the bending direction aligned with the long dimension of the tablet. The OLED tablet was set to white screen display (R=0, G=0, B=0), and the angle was changed from an oblique direction to the normal direction of the display screen, and the display screen was rotated in the in-plane direction while visually observing the screen, and the occurrence of rainbow spots was judged as follows. Color unevenness observed only on the tablet used was excluded from the judgment. ◎: No rainbow spots observed from any direction. ○: Very faint rainbow spots can be observed in some directions. △: Faint rainbow spots can be observed in some directions but over a fairly wide area. ×: Rainbow spots are clearly visible in a wide range, but only in some directions.

[0091] (Preparation of polyethylene terephthalate pellets (a)) A continuous esterification reaction apparatus consisting of a three-stage complete mixing tank equipped with an agitator, a partial condenser, a raw material inlet, and a product outlet was used as the esterification reaction apparatus. TPA was set at 2 tons / hr, EG at 2 moles per mole of TPA, and antimony trioxide at an amount such that Sb atoms would be 160 ppm relative to the PET produced. These slurries were continuously supplied to the first esterification reaction vessel of the esterification reaction apparatus and reacted at normal pressure for an average residence time of 4 hours at 255°C. Next, the reaction product in the first esterification reactor was continuously taken out of the system and fed to a second esterification reactor, EG distilled from the first esterification reactor was fed into the second esterification reactor in an amount of 8% by mass relative to the produced polymer (produced PET), and an EG solution containing magnesium acetate in an amount such that Mg atoms were 65 ppm relative to the produced PET and an EG solution containing TMPA in an amount such that P atoms were 20 ppm relative to the produced PET were added, and reacted at normal pressure for an average residence time of 1.5 hours at 260° C. Next, the reaction product in the second esterification reactor was continuously taken out of the system and fed to a third esterification reactor, and an EG solution containing TMPA in an amount such that P atoms were 20 ppm relative to the produced PET was added, and reacted at normal pressure for an average residence time of 0.5 hours at 260° C. The esterification reaction product produced in the third esterification reaction vessel was continuously supplied to a three-stage continuous polycondensation reaction apparatus to carry out polycondensation, and was then filtered through a stainless steel sintered filter medium (nominal filtration accuracy: 90% cut of 5 μm particles) to obtain polyethylene terephthalate pellets (a) having an intrinsic viscosity of 0.62 dl / g.

[0092] (Preparation of polyethylene terephthalate pellets (b)) In the same manner as in the production process of polyethylene terephthalate pellets (a), except for adjusting the residence time of the third esterification reaction, the intrinsic viscosity was adjusted to 0.580 dl / g to obtain polyethylene terephthalate pellets (b).

[0093] (Preparation of polyethylene terephthalate pellets (c)) The polyethylene terephthalate pellets (a) were subjected to solid-phase polymerization at 220° C. for various times under a reduced pressure of 0.5 mmHg using a rotary vacuum polymerization apparatus to produce polyethylene terephthalate pellets (c) having an intrinsic viscosity of 0.75 dl / g.

[0094] (Polymerization of urethane resin) A four-neck flask equipped with a stirrer, a Dimroth condenser, a nitrogen inlet tube, a silica gel drying tube, and a thermometer was charged with 72.96 parts by mass of 1,3-bis(isocyanate methyl)cyclohexane, 12.60 parts by mass of dimethylolpropionic acid, 11.74 parts by mass of neopentyl glycol, 112.70 parts by mass of polycarbonate diol having a number average molecular weight of 2000, and 85.00 parts by mass of acetonitrile and 5.00 parts by mass of N-methylpyrrolidone as a solvent, and stirred at 75°C for 3 hours under a nitrogen atmosphere, and it was confirmed that the reaction liquid reached a predetermined amine equivalent. Next, the reaction liquid was cooled to 40°C, and then 9.03 parts by mass of triethylamine was added to obtain a polyurethane prepolymer D solution. Next, 450g of water was added to a reaction vessel equipped with a homodisper capable of high-speed stirring, and the temperature was adjusted to 25°C. While stirring and mixing at 2000 min-1, an isocyanate group-terminated prepolymer was added and dispersed in water. Thereafter, acetonitrile and a portion of the water were removed under reduced pressure to prepare a water-soluble polyurethane resin (A) having a solid content of 35 mass %.

[0095] (Polymerization of Water-soluble Carbodiimide Compounds) In a flask equipped with a thermometer, a nitrogen gas inlet tube, a reflux condenser, a dropping funnel, and a stirrer, 200 parts by mass of isophorone diisocyanate and 4 parts by mass of 3-methyl-1-phenyl-2-phospholene-1-oxide as a carbodiimide catalyst were added, and the mixture was stirred for 10 hours at 180°C under a nitrogen atmosphere to obtain isocyanate-terminated isophorone carbodiimide (polymerization degree = 5). Next, 111.2 g of the obtained carbodiimide and 80 g of polyethylene glycol monomethyl ether (molecular weight 400) were reacted at 100°C for 24 hours. Water was gradually added to the mixture at 50°C to obtain a yellow, transparent, water-soluble carbodiimide compound (B) with a solid content of 40% by mass.

[0096] (Preparation of Coating Solution for Forming Adhesion Layer) The following coating materials were mixed to prepare a coating solution. Water 16.97 parts by mass Isopropanol 21.96 parts by weight Polyurethane resin (A) 3.27 parts by weight Water-soluble carbodiimide compound (B) 1.22 parts by mass Particles 0.51 parts by mass (Silica sol with average particle size of 40 nm, solid content concentration of 40% by mass) Surfactant 0.05 parts by weight (Silicone-based, solids concentration 100% by mass)

[0097] (Preparation of hard coat coating solution a) 0.1 parts by weight of a leveling agent (BYK307, 100% concentration, manufactured by BYK Japan) was added to 100 parts by weight of a hard coat material (Opstar (registered trademark) Z7503, manufactured by JSR Corporation, concentration 75%), and the mixture was diluted with methyl ethyl ketone to prepare a hard coat coating solution a with a solid content concentration of 40% by weight.

[0098] Example 1 Pellets of polyethylene terephthalate (a) were fed to an extruder and melted at 285°C. The polymer was filtered through a stainless steel sintered filter medium (nominal filtration accuracy 10μm particles 95% cut), extruded from a die in the form of a sheet, and then contacted with a casting drum with a surface temperature of 30°C using an electrostatic casting method to cool and solidify, producing an unstretched film. The unstretched film was uniformly heated to 75°C using a heating roll, heated to 85°C using a non-contact heater, and roll-stretched (longitudinal stretching) 1.4 times. The above-mentioned coating solution for forming an easy-adhesion layer was applied to both sides of the obtained uniaxially stretched film by a roll coating method, and then dried at 80°C for 20 seconds. The coating amount after the final (biaxial stretching) drying was 0.06g / m 2The film was then introduced into a tenter, preheated at 105°C, transversely stretched 4.0 times at 95°C, fixed at the width, heat-set at 230°C for 5 seconds, and further relaxed in the width direction by 4% at 180°C to obtain a polyethylene terephthalate film with a thickness of 50 μm. The evaluation results are shown in Table 1.

[0099] (Examples 2 to 3) A polyester film was obtained in the same manner as in Example 1, except that the stretching ratio in the longitudinal direction was changed to that shown in Table 1.

[0100] Example 4 A polyester film was obtained in the same manner as in Example 1, except that the stretching ratio in the width direction was changed to 4.4 times and the heat setting temperature was changed to 220°C.

[0101] (Examples 5 to 6) A polyester film was obtained in the same manner as in Example 4, except that the stretching ratio in the longitudinal direction was changed as shown in Table 1.

[0102] Example 7 A polyester film was obtained in the same manner as in Example 1, except that the stretching ratio in the width direction was changed to 5.5 times and the heat setting temperature was changed to 190°C.

[0103] (Examples 8 to 9) A polyester film was obtained in the same manner as in Example 7, except that the stretching ratio in the longitudinal direction was changed as shown in Table 1.

[0104] Example 10 A polyester film was obtained in the same manner as in Example 5, except that in the production process of Example 5, after the film was stretched in the longitudinal direction, a 10% relaxation heat treatment was carried out at 100°C.

[0105] Example 11 In the manufacturing process of Example 5, the clips were released at 200°C after heat setting, and a relaxation heat treatment was performed in the longitudinal and width directions, but the same procedure was followed to obtain a polyester film. The tenter speed and the take-up roll speed were adjusted so that the relaxation rate in the longitudinal direction was 3%. The relaxation in the width direction was left in a free state.

[0106] Example 12 A polyester film was obtained in the same manner as in Example 1, except that the temperature during longitudinal stretching was changed to 75°C and the heat setting temperature was changed to 220°C.

[0107] (Example 13) A polyester film was obtained in the same manner as in Example 1, except that the temperature during longitudinal stretching was changed to 75°C, the stretching ratio was changed to 1.2 times, and then the stretching ratio was changed to 5.0 times in the width direction.

[0108] Example 14 A polyester film was obtained in the same manner as in Example 3, except that the longitudinal stretching in Example 3 was a two-stage stretching in which the first stage stretching ratio was 1.2 times and the second stage stretching ratio was 1.67 times. The total longitudinal stretching ratio was about 2.0 times.

[0109] Example 15 A polyester film was obtained in the same manner as in Example 5, except that the preheating temperature during widthwise stretching was changed to 95°C and the heat setting temperature was changed to 190°C.

[0110] (Example 16) A polyester film was obtained in the same manner as in Example 2, except that the stretching in the width direction in Example 2 was changed to two-stage stretching, the stretching ratio in the first stage was 1.5 times, the stretching ratio in the second stage was 4.0 times, and the heat setting temperature was changed to 190° C. The total stretching ratio in the width direction was 6.0 times.

[0111] (Examples 17 to 18) A polyester film was obtained in the same manner as in Example 2, except that the thickness was changed as shown in Table 1. Here, the polyester film obtained in Example 17 did not necessarily give good results in the rainbow spot observation, but the polyester film in the present invention can be used in any part of a folding display, and for example, the polyester film obtained in Example 17 can be preferably used in applications such as a back surface protective film for a folding display that is not related to rainbow spots.

[0112] (Example 19) A polyester film was obtained in the same manner as in Example 1, except that the relaxation heat treatment in the width direction was not carried out in the production process of Example 1.

[0113] (Example 20) An unstretched film was prepared in the same manner as in Example 1, and the unstretched film was preheated at 75°C in a tenter and stretched laterally to 1.4 times at 85°C. The above-mentioned coating liquid for forming an easy-adhesion layer was applied to both sides of the obtained uniaxially stretched film by roll coating, and then dried at 80°C for 20 seconds. The final coating amount after drying (after biaxial stretching) was 0.06 g / m 2 The film was uniformly heated to 105°C using a heating roll, heated to 95°C using a non-contact heater, and roll-stretched (longitudinal stretching) at 4.0 times the original size. The film was fixed in width and heat-set at 230°C for 5 seconds to obtain a polyethylene terephthalate film with a thickness of 50 μm. The subsequent steps were the same as in Example 1 to obtain a hard coat film.

[0114] Comparative Example 1 A polyester film was obtained in the same manner as in Example 1, except that the film was not stretched in the longitudinal direction but was stretched only in the width direction, that is, uniaxially stretched in the transverse direction.

[0115] Comparative Example 2 A polyester film was obtained in the same manner as in Example 7, except that the film was not stretched in the longitudinal direction but was stretched only in the width direction, that is, uniaxially stretched in the transverse direction.

[0116] (Comparative Examples 3 to 7) A polyester film was obtained in the same manner as in Example 1, except that the heat setting temperature was changed to 220° C., and the PET pellets and thickness were as shown in Table 1. As described above, in Comparative Examples 3 to 7, the heat setting temperature was lower than that in Example 1, and the combination of the longitudinal and transverse stretching ratios was not the best within the preferable range of conditions. As shown in Table 1, the refractive index in the thickness direction increased, the indentation depth after the test force was removed was large, and the pencil hardness after the hard coat layer was laminated was smaller than that in each Example.

[0117] Comparative Example 8 A polyester film was obtained in the same manner as in Example 1, except that the stretching ratio in the longitudinal direction was changed to 2.7 times and the heat setting temperature was changed to 220°C.

[0118] Comparative Example 9 A polyester film was obtained in the same manner as in Example 1, except that the stretching ratio in the longitudinal direction was changed to 3.4 times.

[0119] Comparative Example 10 A polyester film was obtained in the same manner as in Example 4, except that the heat setting temperature was changed to 100°C.

[0120] Comparative Example 11 A polyester film was obtained in the same manner as in Example 13, except that the longitudinal stretching temperature was changed to 130°C.

[0121] Comparative Example 12 A polyester film was obtained in the same manner as in Example 1, except that the preheating temperature in the width direction was changed to 120°C.

[0122] Comparative Example 13 A polyester film was obtained in the same manner as in Example 13, except that the stretching ratio in the transverse direction was changed to 5.5 times and the heat setting temperature was changed to 230°C.

[0123] Using a Mayer bar, hard coat coating solution a was applied to one side of the film prepared above so that the film thickness after drying would be 5 μm, and the film was dried at 80° C. for 1 minute, and then irradiated with ultraviolet light (accumulated light amount 200 mJ / cm 2 ).2 ) to obtain a hard coat film.

[0124] The hard coat film was attached to an organic EL module via a 25 μm thick adhesive layer, and a smartphone-type folding display that can be folded in half at the center of the entire display with a radius of 3 mm, which corresponds to the bending radius in FIG. 1, was created. The hard coat film was arranged on the surface of one continuous display through the folding portion, and the hard coat layer was arranged so as to be located on the surface of the display. The hard coat films of each embodiment were satisfactory in operation and visibility as a smartphone that can be folded in half at the center and carried around. In addition, the surface was not dented by external force. On the other hand, the folding display using the hard coat films of each comparative example seemed to cause image distortion at the folding portion of the display as the frequency of use increased, which was not very preferable. In addition, some of the displays had dents and scratches on the surface.

[0125] [Table 1] [Industrial Applicability]

[0126] A folding display using the polyester film or hard coat film for folding displays of the present invention maintains mass productivity, and the polyester film or hard coat film located on the surface of the folding display does not deform after repeated folding, so that no image distortion occurs at the folded part of the display. In particular, a mobile terminal device or image display device equipped with a folding display using the polyester film or hard coat film of the present invention as a surface protective film provides beautiful images, is highly functional, and has excellent convenience such as portability. [Explanation of symbols]

[0127] 1: Foldable display 11: Bending radius 2: Polyester film for surface protection of folding displays 21: Folding section 22: Bending direction (direction perpendicular to the folding part)

Claims

1. A polyester film for a foldable display that satisfies the following conditions: (1) The refractive index in the bending direction is 1.590 to 1.620 (2) The refractive index in the direction of the fold is 1.670 to 1.700 (3) A refractive index in the thickness direction is 1.520 or less. (4) Density is 1.380 g / cm 3 End (5) The polyester film is a biaxially oriented polyethylene terephthalate film. (Here, the bending direction refers to the direction perpendicular to the fold when folding the polyester film.)

2. 2. The polyester film for folding displays according to claim 1, having a total light transmittance of 85% or more, a haze of 3% or less, and a maximum heat shrinkage rate of 6% or less.

3. The polyester film for folding displays according to claim 1 , further comprising an easy-adhesion layer on at least one surface of the polyester film.

4. The polyester film for folding displays according to claim 1, having an in-plane retardation (Re) of 3000 to 30000 nm.

5. A hard coat film for a folding display, comprising the polyester film for a folding display according to any one of claims 1 to 4, and a hard coat layer having a thickness of 1 to 50 µm on at least one side of the polyester film for a folding display.

6. A foldable display in which the hard coat film for a foldable display according to claim 5 is arranged as a surface protective film so that the hard coat layer is positioned on the surface, and a single continuous hard coat film is arranged through the folding portion of the foldable display.

7. A mobile terminal device having the foldable display according to claim 6.

Citation Information

Patent Citations

  • Biaxially oriented polyethylene terephthalate film

    CN103249540A

  • Easily adhesive polyester film for optical use

    JP2014065887A

  • Resin laminate plate and touch panel

    JP2017129868A

  • Biaxially oriented polyethylene terephthalate film

    US20130323487A1

  • Biaxially oriented polyethylene terephthalate film

    WO2012114988A1